IP Policy Framework- A Tool for IP Policy Development (Journal of Intellectual Property Rights (JIPR), 2023)
Innovation and scientific developments are the bases for economic growth. Academic and research organizations are keycontributors to this development. These are the intellectual capital hubs rich in innovation capital. Innovation capital isresponsible for inventions and innovations that can be protected by using the legal instrument to create intellectual property(IP). These IP rights creation and management is smooth if there is an organisational IP Policy which will address variousIP-related issues. Hence, careful drafting of IP Policy is an indispensable activity of an organization. However, this isusually ignored by academic and research organisations in developing nations may be due to unawareness about itsimportance and unavailability of IP experts for drafting IP Policy. There are various earlier efforts to push theseorganisations to develop their own IP Policy including IP Policy guidelines developed by Government bodies. However, inspite of these efforts, IP Policy is not created by most of the academic and research organisations in the country till date.After examining the reasons for the non development of IP Policy, a new “IP Policy Framework” is proposed to overcomethese problems. The IP policies have been analysed through exploratory research methodology for various organizations inthe India and across various organisations from developed nations.